Analisis Pelaksanaan Peran, Fungsi dan Wewenang Governing Body di Rumah Sakit Islam NU Demak - Rudi Ansyah; Sarsintorini Putra; Sudiro Sudiro (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Hospital health services have a high level of complexity and are prone to conflicts both inside and outside the hospital. The implementation of quality management is still a lot of obstacles faced evidenced by many hospital staff who do not know about quality management, frequent conflicts and lack of clarity of coordination, communication and information channels. The purpose of this research is to analyze the implementation of the role, function and authority of governing body, director, medical committee and nursing committee, quality management implementation, quality leadership and hospital barrier in order to improve quality management of NU Demak Islamic Hospital. This research design using descriptive method with qualitative approach. The main informants were the governing body, the director, the medical committee and the nursing committee and the triangulation informant were the executing physician, the nurse and the chairman of the quality team. Data were collected by in-depth interview techniques. Processing and data analysis using content analysis. The results show the role and function governing body has been implemented but the authority has not been implemented optimally. The role and authority of the director have been implemented but the function has not been implemented optimally. The role and function of the medical committee has been implemented but the authority has not been implemented optimally. The role and function of the nursing committee has not been implemented optimally but the authority has been implemented. Quality planning has been implemented, but quality control and improvement has not been implemented optimally. Building vision, inspiring processes, mobilizing human resources and becoming a model has been implemented. It is recommended to allocate budgets for the training of the ex-house training, to make guidelines for recording and reporting, to make guidance on performance evaluation of officers, to create a checklist of performance evaluation and to make an assessment of internal satisfaction